Radiographers and radiation protection: education, training and CPD - Lança, Luís (2012)
The increasing use of ionizing radiation for medical purposes emphasizes the concern about safety and justification of using ionizing radiation. This is linked with the use of new and high-dose X-ray technology (particularly CT). According to the UNSCEAR 2010 Report the total number of diagnostic medical examinations (both medical and dental) is estimated to have risen from 2.4 billion (period 1991–1996) to 3.6 billion (period 1997– 2008) - a marked increase in collective doses. An appropriate use of technology aiming diagnostic or therapy and respecting the ALARA principle is a mandatory requisite to safely perform any radiological procedure. Radiation protection is thus, a concern of all specialists in the radiology field ( radiologists, radiographers, medical physicists, among other professional groups). The importance of education and training of these professionals in reducing patients’ doses while maintaining the desired level of quality in medical exposures, as well as precise therapeutic treatments is well recognized. Education, training and continuing professional development (CPD) constitute a triad pointing towards the radiographers’ development of competences in the radiation protection field. This presentation excludes the radiographer role and competences in the fields of ultrasonography and MRI.